Effectiveness of short-term modified Atkins diet and classic ketogenic diet in pediatric intractable epilepsy: a systematic review and meta-analysis - Maulena, Ufik; Agustina, Nenden Nursyamsi; Mangunatmadja, Irawan (Paediatrica Indonesiana, 2025)
Background Dietary treatments such as the classic ketogenic diet (cKD) and the modified Atkins diet (MAD) have shown promise in the medical management of refractory epilepsy. Objective To investigate the efficacy of the modified Atkins diet and classic ketogenic diet in managing intractable epilepsy in children by systematic review and meta-analysis. Methods This systematic review followed the preferred reporting items for systematic review and meta-analysis (PRISMA). We carried out an overview on Google Scholar, Scopus, and PubMed to find pertinent studies. Only researches that directly compared cKD and MAD were included in this study. A random-effect model was used to calculate pooled effect sizes as risk ratios (RRs) with 95% confidence intervals (CIs). The primary outcome was seizure frequency reduction (SFR) >50%. Secondary outcomes included SFR >90% and seizure freedom. Results Of 1,013 articles screened, 7 studies with a total of 455 patients (214 on MAD and 241 on cKD) met the inclusion criteria. There were no significant differences in the proportion of patients with seizure frequency reduction (SFR >50% (RR 1.12; 95%CI 0.70 to 1.80; P=0.64), SFR >90% (RR 0.83; 95%CI 0.57 to 1.20; P=0.33, respectively), or those who were seizure free (RR 1; 95%CI 0.7 to 1.42; P=0.99, respectively). However, each study in our review revealed that both cKD and MAD groups achieved significantly more SFR >50%,  SFR >90%, and seizure-free than before the diet. No improvement were seen in these outcomes after diet intervention. Conclusion In managing refractory childhood epilepsy, the efficacy of cKD and MAD are not significantly different.